Relationship of Risky Internet Use with Parental Depression and Anxiety in a Sample of Turkish Adolescents with Attention Deficit Hyperactivity Disorder - Songül Derin; Muhammed Ersin; Saliha Büşra Selman (Psikiyatride Güncel Yaklaşımlar, 2023)
Parental mental health has a significant impact on adolescent well-being, including their engagement in problematic behaviors such as risky internet use. However, limited research has examined the association between parental mental health and risky internet use (RIU) in adolescents, particularly those with attention-deficit/hyperactivity disorder (ADHD). To address this gap, this study investigated the relations between parental depression and anxiety symptoms and RIU in adolescents with ADHD. A sample of 100 participants (mean age = 13.6 years; 27% female) diagnosed with ADHD was included. Parental depression and anxiety symptoms were assessed using the Beck Depression and Beck Anxiety Inventories, while adolescents' RIU was measured using Young's Internet Addiction Scale. Participants with scores exceeding 50 on the scale were classified as having RIU. After controlling for adolescent gender, parental education levels, and income, the results revealed that both parental depressive (β = 0.09) and anxiety symptoms (β = 0.06) significantly predicted an elevated risk of RIU in adolescents with ADHD. These findings highlight the substantial role of parental depression and anxiety as risk factors for RIU in this population. Understanding these associations can inform the development of targeted interventions to mitigate the impact of parental mental health on adolescent RIU and promote better outcomes for individuals with ADHD.